Paghahambing Sa Wikang Sinama Ng Mga Badjao Sa Wikang Filipino At Ingles Sa Konstekstong Ponolohiya, Morpolohiya At Sintaksis - Necita Tayong (Philippine Association of Institutions for Research, Inc., 2017)
This study is a phonologic, morpological and syntax analysis in the Sinama - Badjao language compared to Filipino and English. This study aims to answer specific questions: What is the structure of phonology of Sinama-Badjao according to the method of articulation and point articulation? What is the structure of the Sinama-Badjao morphology by fiscal, repetition and synthesis? What is the syntax structure of the Sinama-Badjao language according to the terms of identification and transactional rules: simple "simplex, interrelated, conditional clause, adverb, question and relationship/relativization. What is differences and similarities in phonological morphology and Sinama-Badjao syntax in English and Filipino? What curriculum decision can be planned for the understanding of the Sinama-Badjao group? Qualitative methodology of this methodology used in this study with a design analysis of language phenomenology due to the examination of phonemees, English and Filipino morphemes. The study of the Sinama language structure is the focus of the fukos in the context of the cultural environment of this ethnic group. From the findings of this researcher, the following conclusions have been drawn: The Sinama -Badjao language phonology structure is very similar to the structure of the Filipino language. Divided into vowels and consonants. There are five (5) vowels and sixteen consonants in Sinama-Badjao. The structure of the Sinama-Badjao language morphology is likewise similar to the Sinama language similar to the Filipino language developed by the inclusion of free morphemes and independent morphemes.